Rancang Bangun Mesin Pembuat Popcorn Dengan Perasa Skala Rumah Tangga Berbasis Arduino - Yessica Greselda; Dhika Aditya Purnomo; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Indonesia is an agricultural country. One of the largest agricultural commodities in Indonesia is corn. Corn has a high carbohydrate content, Popcorn is an alternative healthy snack made from corn kernels. The process of making popcorn is generally done manually by pouring the corn and seasonings. The manufacturing process can be done with just one button press, and popcorn is ready to be enjoyed using the machine. The new innovation is making an Arduino-based household-scale popcorn machine. The design process using the Ulrich method starts from identifying machine requirements to selecting concepts and design embodiments. Planning and calculations are carried out on the machine design. So the hope is that with this machine this time it can make popcorn production easier in an efficient and ergonomic way. The design of the engine on stir will be analyzed using Fusion 360 Software which will then be made into technical drawings. The machine that has been made will be tested. Based on the results of planning and design using the Ulrich method, design concept 2 was chosen. In testing the Arduino-based household- scale popcorn making machine, the popcorn making process is more automatic in 1 press of a button and produces popcorn 2.45 kg/hour. The total budget needed is IDR 3,104,500.